Analisis Kemampuan Pemecahan Masalah Matematis Siswa Ditinjau dari Self confidence - Fitriyani Hali; Ardiansyah; Deti Sri Rahayu; Dian Ulfa Sari (Arden Jaya Publisher, 2022)
This study aims to describe the mathematical problem solving ability of students in class VIII MTs Negeri 2 Kolaka in terms of self confidence. This type of research is qualitative. The subjects of this study consisted of 48 students of class VIII MTs Negeri 2 Kolaka. The instrument used is a mathematical problem-solving ability test consisting of 4 questions, a self confidence questionnaire consisting of 16 statements, and interview guidelines. The results showed that; 1) The average mathematical problem solving ability of students is 49.29 which is in the low category. Many students who have a high ability score are 4 (8%), students with a moderate ability score are 9 (19%), and many students have a low ability score of 35 (73%); 2) The number of students with high self confidence is 8 students (16%), moderate self confidence is 31 students (65%), and low self confidence is 9 (19%); 3) Students with high self confidence have the highest average ability with an average score of 69.94 with moderate criteria, followed by students with moderate and low self confidence with scores of 48.65 and 28, respectively. ,83 both of which are in the low criteria. Subjects with high self confidence are generally able to understand all indicators of mathematical problem solving, namely understanding problems, planning problems, solving problems, and drawing conclusions. Subjects with moderate self confidence were only able to understand 3 indicators, namely understanding the problem, planning the problem, and drawing conclusions. While the indicators solve the problem the subject is less able to understand these indicators. Subjects with low self confidence are less able to solve problems and on other indicators the subject is unable to understand them. So it can be said that the higher the student's self confidence, the better the problem-solving ability and vice versa.